Breast implant infection with pasteurella canis: First case-report. (September 2019) - Hannouille, J.; Belgrado, J.P.; Vankerchove, S.; Vandermeeren, L.
Abstract: Zoonotic infections represent an uncommon phenomenon. Few people with pets realise the infectious risk this entails. This case describes a Pasteurella canis infection of a breast implant following close contact between a patient and her cat. A 59-year-old woman developed infection of her breast implant 7 months after implantation. Surgical revision was performed after failure of conservative treatment with antibiotics. Perioperative samples from the periprosthetic fluid were positive for P. canis, a Gram-negative coccobacillus that is present in the oropharyngeal commensal flora of cats and dogs. History revealed that the patient owned a cat for 2 years. This case highlights the possible risk of zoonotic infections in humans with protheses following close contact with a cat. Antibiotic therapy and surgical revision, with or without removal of the prosthesis constitute the cornerstone of treatment in such cases.